Totem-Pole Bridgeless Boost PFC Rectifier Using Series-Parallel Resonant Network - Muhammad, K. S.; Baharom, R.; Seroji, M. N.; Lu, D. D-C. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
A new series-parallel resonant bridgeless boost (SPBBR) power factor correction (PFC) rectifier is proposed in this paper. It is based on a totem-pole bridgeless boost (TPBLB) configuration which allows bi-directional current to flow during resonance to provide soft-switching for all semiconductor devices. Therefore, no additional active switch is needed. The resonant is produced by a resonant network which is placed before the output capacitor. A detailed analysis of the converter operation and control is presented. Design considerations and parameter values determination are also given. Simulation results is used to verify the theoretical analysis of the SPBBR.